Rapid three-dimensional scene modeling by sketch retrieval and auto-arrangement. (May 2017) - Ren, Pu; Fan, Yachun; Zhou, Mingquan; Wang, Zhe; Du, Guoguang; Qian, Lu
Highlights: A completed workflow for rapid 3D outdoor scene modeling is implemented. Sketch-based retrieval is improved by manifold ranking obtaining high accuracy. Energy function is composed by specific constraints designing for outdoor scenes. Auto-arrangement is optimized by PSO-SA algorithm efficiently. Effectiveness is proved by evaluations of practical experiments and user study. Graphical abstract: Abstract: The existing three-dimensional (3D) object layout methods are focused mainly on indoor scenes and they are limited for outdoor applications. In this study, we propose a data-driven method for outdoor scene modeling by using fast retrieval and automatic optimization layout techniques. Unlike the current methods, we first employ an improved manifold ranking algorithm in the sketch-based 3D model retrieval stage, which achieves higher accuracy. Next, according to the particular properties of outdoor architectures, specialized constraints are then proposed to define an energy function, which meets both the functional and aesthetic requirements. Finally, we cast the auto-arrangement as a combinatorial optimization problem, which we solve using an optimization algorithm. In contrast to the earlier version of this method, which was presented at Cyberworlds 2016, this extended version combines simulated annealing and particle swarm optimization algorithms, which have the advantages of rapid convergence and avoiding becoming trapped by local minima. Our experimental results demonstrate that the proposed method is more intuitive and effective for modeling 3D scenes, and can be employed in the actual development of game scenes.